Bridging theory and practice: Performance management in SMEs – the Gun Collection experience - Sudrajat, Yusuf Ahmad; Setiawati, Trias; Putri, Swastuti Amalia; Pujakusuma, Adinda; Setiana, Mira Feby; Maharani, Layalia; Rosyada, Qorri Aina (Asian Management and Business Review, 2025)
This study aims to analyze performance management practices at Gun Collection, a family-owned SME operating in the apparel retail and distribution sector, facing operational challenges and opportunities for growth in local markets. Using a case study approach, this research explores key elements of the performance management system, including performance evaluation, employee development, rewards and compensation, and compliance with labor regulations. Theoretically, this study employs the framework developed by Aguinis (2019), identifying five key dimensions in the performance management process: Prerequisites, Performance Planning, Performance Execution, Performance Assessment, and Performance Review. This research adopts a qualitative case study method. The findings reveal that Gun Collection successfully implements a structured performance management system through regular evaluations, technical and interpersonal training programs, contribution-based rewards, and adherence to labor regulations. This holistic approach enhances individual productivity and team collaboration and strengthens a competitive and sustainable organizational culture. However, the study also highlights challenges such as limited resources and the need for adaptation in a dynamic business environment. The study contributes theoretically by expanding the understanding of performance management implementation in SMEs, particularly in developing countries. Practically, the findings guide SME practitioners to design relevant and effective performance management systems to support organizational growth and sustainability.